Death Inequality During the First Year of Life in Morocco: A Macro Level Analysis - LOUDGHIRI, Khadija; BAKASS, Fatima; FAZOUANE, Abdesselam (Advances in Social Sciences Research Journal, 2022)
Disparities in child mortality are a reality in Morocco. These disparities coexist with inequalities in: (i) the availability of primary health care (PHCs); (ii) the socioeconomic status of the population as reflected by the prevalence of various forms of poverty; as well as (iii) fertility levels (TFRs) and the status of women in literacy and employment rates. Despite its limitations, this research provides a macro-level understanding of the link between infant mortality and a range of aggregates (political, economic, social and demographic).The metadata collected in the 2014 census (RGPH-2014) RGPH-2014 was used to construct a provincial proxy indicator of infant mortality by area of residence.This is considered as a dependent variable that we have tried to explain by the above-mentioned indicators. This is considered as a dependent variable that we have tried to explain by the above-mentioned indicators. The latter indicators reflect the socio-economic conditions prevailing in each of the provinces by area of residence. In addition, they give information on the availability of basic health services and on the woman’s status. A key finding is that the level of current fertility as measured by the TFR negatively affects child survival. With a statistically significant regression coefficient of 2.912 (Pvalue =0.000), it can be argued that high fertility increases the risk of infant mortality. In turn, the prevalence of overall poverty also has a statistically significant effect on infant survival (β= -0.213 with a pvalue =0.029).